An agent-based platform for simulating complex human–aquifer interactions in managed groundwater systems. (November 2015) - Castilla-Rho, J.C.; Mariethoz, G.; Rojas, R.; Andersen, M.S.; Kelly, B.F.J.
Abstract: This paper presents and illustrates FlowLogo, an interactive modelling environment for developing coupled agent-based groundwater models (GW-ABMs). It allows users to simulate complex socio-environmental couplings in groundwater systems, and to explore how desirable patterns of groundwater and social development can emerge from agent behaviours and interactions. GW-ABMs can be developed using a single piece of software, addressing common issues around data transfer and model analyses that arise when linking ABMs to existing groundwater codes. FlowLogo is based on a 2D finite-difference solution of the governing groundwater flow equations and a set of procedures to represent the most common types of stresses and boundary conditions of regional aquifer flow. The platform is illustrated using a synthetic example of an expanding agricultural region that depends on groundwater for irrigation. The implementation and analysis of scenarios from this example highlight the possibility to: (i) deploy agents at multiple scales of decision-making (farmers, waterworks, institutions), (ii) model feedbacks between agent behaviours and groundwater dynamics, and (iii) perform sensitivity and multi-realisation analyses on social and physical factors. The FlowLogo interface allows interactively changing parameters using 'tuneable' dials, which can adjust agent decisions and policy levers during simulations. This flexibility allows for live interaction with audiences (role-plays), in participatory workshops, public meetings, and as part of learning activities in classrooms. FlowLogo's interactive features and ease of use aim to facilitate the wider dissemination and independent validation of GW-ABMs. Highlights: A modelling tool to develop coupled agent-based and groundwater simulations (GW-ABMs). Integrates the most common functionalities of groundwater codes to NetLogo. Allows the design of agents and their behavioural traits in an interactive fashion. Tests trade-offs between management objectives in complex groundwater systems. An accessible tool to apply the principles of complex systems to groundwater problems.